1993
DOI: 10.1300/j069v12n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Medical Maintenance:

Abstract: In a one year study, 130 methadone maintained subjects with a six month history of good treatment performance were assigned randomly to an experimental condition of one monthly non-random urine screen, one monthly counseling session, one monthly doctor visit, two times per month methadone pick up, a quarterly true random urine screen and participation in a diversion control program or to a control condition of staying under standard conditions for six months and then being transferred to the experimental condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 1 publication
2
30
0
Order By: Relevance
“…Despite positive reports evaluating the use of MMM interventions in patients with long-term stable and positive treatment responses (Fiellin et al, 2001;Novick et al, 1994; Salsitz et al, 2000;Schwartz, Brooner, Montoya, Currans, & Hayes., 1999;Senay et al, 1993), adoption of the intervention has been slow. At least two unresolved issues may be hindering the broader adoption of this intervention in community-based treatment settings: The first issue involves the lack of research on effective management strategies for MMM patients who relapse to drug use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite positive reports evaluating the use of MMM interventions in patients with long-term stable and positive treatment responses (Fiellin et al, 2001;Novick et al, 1994; Salsitz et al, 2000;Schwartz, Brooner, Montoya, Currans, & Hayes., 1999;Senay et al, 1993), adoption of the intervention has been slow. At least two unresolved issues may be hindering the broader adoption of this intervention in community-based treatment settings: The first issue involves the lack of research on effective management strategies for MMM patients who relapse to drug use.…”
Section: Introductionmentioning
confidence: 99%
“…At least two unresolved issues may be hindering the broader adoption of this intervention in community-based treatment settings: The first issue involves the lack of research on effective management strategies for MMM patients who relapse to drug use. Patients in previous studies who relapsed and could not be adequately treated in an office-based setting were returned to methadone maintenance clinics and not allowed to return to the MMM schedule (Fiellin et al, 2001;Salsitz et al, 2000;Schwartz et al, 1999;Senay et al, 1993). This amounts to a permanent intensification of treatment services that is likely unnecessary in many instances and perhaps to a more punitive versus therapeutic response to otherwise expected lapses to drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Two published studies have reported successful medical maintenance programs in which stabilized (e.g. no evidence of active drug use for 1 or more years) methadone-maintained patients were transferred from care in narcotic treatment programs to medical maintenance settings (76,77,96). These programs have reported retention rates of 73%-85% for up to 3 years in some patients (77,96).…”
Section: Methadone Maintenance In Physician's Officesmentioning
confidence: 99%
“…no evidence of active drug use for 1 or more years) methadone-maintained patients were transferred from care in narcotic treatment programs to medical maintenance settings (76,77,96). These programs have reported retention rates of 73%-85% for up to 3 years in some patients (77,96). These favorable statistics suggest that medical maintenance programs may be used to expand access to methadone maintenance and reduce overcrowding in narcotic treatment programs.…”
Section: Methadone Maintenance In Physician's Officesmentioning
confidence: 99%
“…In the UK and Australia, this spectrum of opioid agonist treatment intensity across different settings is well established (Byrne & Wodak 1996;Luger, Bathia, Alcorn, & Power, 2000;Strang et al, 2005). Initial reports from such office-based initiatives in the United States (known as methadone medical maintenance [MMM]) demonstrated their feasibility and effectiveness (DesJarlais, Joseph, Dole, & Nyswander, 1985;Novick et al, 1994;Novick et al, 1988;Senay et al, 1993). Two randomized controlled trials demonstrating comparable outcomes at 6 months between the MMM approach and standard methadone maintenance have been published (Fiellin et al, 2001;King et al, 2002).…”
Section: Introductionmentioning
confidence: 99%